A Dermal Cream of Coenzyme Q10 and Kojic Acid - Kumar, Varsha; Kumar, Amit (International Journal of Psychosocial Rehabilitation, 2019)
UV radiation is responsible for up to 80% of premature skin aging. Oxidative stress is the major factor in skin aging caused by UV radiation. Therefore, there is a necessity to produce a safe and effective topical antioxidant method, which would not only reduce the likelihood of skin aging but will also have whitening benefits in addition to skin rejuvenation. Coenzyme Q10, a fat-soluble vitamin like substance, is a strong antioxidant present in almost every cell of the human body. The antioxidant properties of Coenzyme Q10 help to significantly reduce oxidative tissue damage. Kojic acid is an antibiotic produced by many species of Aspergillus and Penicillum in an aerobic process from a wide range of carbon sources. Kojic acid has been extensively used as a cosmetic agent with an excellent whitening effect because it inhibits tyrosinase. In this paper pharmaceutical composition of a dermal cream having combination of Coenzyme Q10 and Kojic acid for treating, preventing, minimizing, and/or diminishing signs of aging and exerting skin whitening effect. Therefore, in the present innovation, a new and revolutionary prescription dermal cream has been developed for the prevention of ageing and to exert skin whitening effect